Upaya Meningkatkan Aktivitas Belajar Matematika Peserta Didik Kelas VII pada PJJ Melalui Leksimo - Nila Sari Latif (Jurnal Didaktika Pendidikan Dasar, 2021)
The success of distance learning (PJJ) in mathematics requires teachers to be able to activate students in learning. This study was conducted to determine the increase in student activity in PJJ through using reflection sheets and emoji symbols in mathematics subjects through LKPD with Leksimo. This research is classroom action research, consisting of planning, action implementation, observation, and reflection stages in two cycles using LKPD with Leksimo. Research data were collected through observation and reflection sheets at the end of each cycle and then analyzed by qualitative and quantitative analysis. The results showed that the use of LKPD with Leksimo could activate students in the PJJ from the moderately active category with a percentage of 33.33% in the first cycle increasing to 58.33% with the active category in the second cycle. The emotional condition of students is very good in understanding and enthusiastic about doing assignments from 35.48% in the first cycle to 54.84% in the second cycle. Students who found obstacles or there was confusion in understanding assignments decreased from 25.81% to 6.45%, which means that teachers can help students overcome obstacles to actively participate in learning with the emoji column on the LKPD. The increase in student activity was also marked by filling out the reflection sheet which showed an increase in parental control and supervision from 29% in cycle I to 71% in cycle II.